Validação de um instrumento de triagem para identificação de filhos de alcoolistas, aplicável por pessoal não especializado - Fioretto, Amanda Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Psychoactive substances, including alcohol, are considered a major public health problem in almost all over the world, however it hasn't been given the proper importance it deserves. According to the World Health Organization, about 40% of the population of the world over the age of 15 die as a result of the serious consequences of this drinking. In Brazil, alcohol is the most used licit drug,and it is associated with harms to the body, to the mind and to the social context. Alcoholism is a disease with a high transgenerational rate, particularly in cases of paternal alcoholism, so that children of alcoholic fathers may have a four times higher risk of becoming alcoholics as adults, in addition to risks of developing behavioral, psychiatric problems and learning disabilities; it also can affect family relationship. The aim of this research is to validate quantitatively the Children of Alcoholic Screening Test (CAST) instrument in Brazil, besides testing the relation between parental alcoholism and the test scores obtained by their children, so it can be used by non-specialist staff. The test was performed in 45 children / adolescents within the 10 to 17 years age range. The results obtained indicate that TEFA (portuguese translation of CAST) is applicable in Brazil by non-specialist staff, helping to identify, through their children, alcoholic parents in early stages of their alcohol problems, and allowing also a closer follow up of these children in order to preventing the development of future problems

As substâncias psicoativas, entre as quais o álcool, são consideradas um grande problema de saúde pública em praticamente todo o mundo, fato que não está sendo considerado com devida importância. De acordo com a Organização Mundial de Saúde, cerca de 40% da população mundial acima de 15 anos de idade morrem em decorrência das consequências graves deste uso. No Brasil, o álcool é a droga lícita mais consumida, sendo associada a danos no âmbito orgânico, psicológico e social. O alcoolismo, além de ser considerado patológico, está relacionado à uma alta taxa transgeracional, e as piores consequências estão ligadas ao alcoolismo paterno, de forma que os filhos destes podem apresentar um risco quatro vezes maior de se tornarem alcoolistas quando adultos, além de trazer riscos para o desenvolvimento de problemas comportamentais, psiquiátricos e dificuldades escolares, chegando a afetar o equilíbrio relacional da família. Desta forma, o objetivo desta pesquisa visa validar quantitativamente o instrumento Children of Alcoholic Screening Test (CAST) no Brasil, além de testar a relação entre alcoolismo dos pais e a pontuação do teste obtida pelos seus respectivos filhos, para que o mesmo possa ser utilizado por pessoal não especializado. Participaram desse estudo 45 crianças/adolescentes entre 10 anos completos e 18 anos incompletos. Concluímos que, de acordo com os resultados obtidos, o instrumento TEFA (tradução de CAST), é válido para ser usado no Brasil por pessoal não especializado, pois além de permitir nos levar até os pais alcoolistas antes que os mesmos estejam com problemas graves de saúde, também permite observar mais de perto esses filhos focando a prevenção do desenvolvimento de futuros problemas
Validation of a screening instrument to identifity children of alcoholic people, applicable by non-specialist staff
Keywords: Adolescentes; Alcoolismo - Prevenção; Jovens - Uso de álcool; Crianças; Pais e adolescentes; Psicotropicos; Alcoholism - Prevention